Analysis of Elementary School Students' Interest in Participating in Petanque Sports Based on Gender - Wahyudi, Rizky; Karisman, Vicki Ahmad; Friskawati, Gita Febria (Journal of Physical and Outdoor Education, 2024)
There is a lack of information on the development of the sport of petanque, which is classified as a new sport in West Java province, especially at SDN 02 DAGO, Bogor district. The aim of this research is: How to describe the interest of SDN 02 DAGO students in participating in petanque sports based on gender. This research method is descriptive quantitative with a survey approach. Research instruments include questionnaires, structured observation checklists, and measurement instruments used to collect data that can be measured and analyzed statistically. The population in this study was 20 children consisting of students of SDN 02 DAGO. The sample used 20 children consisting of 11 male students and 9 female students. For the sampling technique, total sampling was taken from all 6th grade students and students at SDN 02 DAGO. The results of this research were that male students were very poor with a percentage of 46%, while female students were very good with a percentage of 34%. The conclusion from the findings of this research is that female students are very better than male students